GENDER AND RELIGIOUS IDENTITY: INTERSECTING AXES OF DISCRIMINATION IN THE BREADWINNER ANIMATED MOVIE (2017) - Geni Kurniati; Christy Tisnawijaya (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2022)
This study, entitled “Gender and Religious Identity: Intersecting Axes of Discrimination in The Breadwinner Animated Movie (2017)”, highlights the importance of conceptualizing gender discrimination related to religious identity as inherently shaped by society. By employing the library research method and intersectional theoretical perspectives, this study examines how gender and religious identity are inextricably linked to portray the main character’s experiences of discrimination. The analysis begins with narrative and illustrative data showing how the main character’s background as a daughter and Muslim results in multiple layers of discrimination. Her gender and religious affiliation substantially influence the discrimination. Moreover, bias varies for men and women of different age groups. The main character experiences more discrimination as a teenage girl than her disguised character as a teenage boy. Women are significantly more likely to face gender discrimination than men, but girls are enormous. Hence, this concurrent examination of the main character’s gender and religious identity reveals that she is characterized by high rates of discrimination throughout her childhood; in a way, teenage boys are not. The main character’s experience of discrimination highlights the importance of conceptualizing gender and religious identity as intersecting axes of discrimination